A comparative study of PSI and Curb-65 scoring systems in predicting ICU admissions and mortality in cases of community-acquired pneumonia - Prashant Patil; Arun Tyagi; Manoj Waghmare; A.K. Srivastava; Marcia Waran (International Journal of Medical Research and Review, 2020)
Background:Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide. Despite advanced diagnostic modalities and treatment options, CAP is the fourth leading cause of death in developing countries.Several severity scores have been proposed to guide initial decision making on hospitalization and to predict the outcome. Pneumonia Severity Index (PSI) and CURB 65 are the two most widely used scoring systems to prognosticate pneumonia.Aim: To compare the efficacy of PSI and CURB 65 scoring systems inprognosticating the ICU admission and outcome in cases of CAP.Methodology: This wasan observational study conducted at a tertiary care hospital in westernMaharashtra.A hundred patients of CAP fulfilling the inclusion criteria were enrolled in the study, classified as per CURB 65 and PSI system and their outcome compared.Result: The study subjects comprised of 100 patients (64 men and 36 women) of CAP. Twenty-four patients needed ICU admission.In both PSI and CURB-65 risk scoring systems, the need for intensive care unit (ICU) admission and mortality rates increased progressively with increasing scores.PSI class ≥IV and CURB 65 ≥III had 77.52% and 40.24% sensitivity and 88.46% and 69.48% specificity respectively in predicting ICU admissions. The PSI class ≥IV had more sensitivity and specificity in predicting ICU admission than CURB-65.CURB 65 class III and IV had sensitivity86.59% and 89.64% and specificity 89.64% and 97.54% respectivelyin predicting mortality, while PSI class IV and Vhadsensitivity68.92% and 72.58% and specificity 24.74% and 54.86% respectively. CURB 65 had more sensitivity and specificity than PSI in predicting mortality.Conclusion: The PSI is better in predicting the need for ICU admission and CURB 65 is a better predictor of mortality in cases of community-acquired pneumonia.